Significant increase and escalation of drought-flood abrupt alteration in China's future - Shuai Zheng; Baisha Weng; Wuxia Bi; Denghua Yan; Liliang Ren; Hao Wang (Agricultural Water Management)
Drought-flood abrupt alteration (DFAA) events threaten global food security, exacerbated by global warming, particularly in China. Given this, a more refined and comprehensive analysis of DFAA events in China can provide valuable insights for global mitigation efforts. This study examines the frequency, intensity, and coverage of DFAA events during the historical periods (HIS, 1961–2014) and under future climate projections based on Shared Socioeconomic Pathways (SSPs: SSP126, SSP245, SSP370, SSP585, 2015–2100) using a daily-scale determination method. The results revealed that regions with frequent DFAA events also experience higher intensity and broader impact areas. Compared to HIS, DFAA event frequency, intensity, and coverage increased by 31 %, 3 %, and 37 % under SSPs, reaching 7.31 events/year, 1.069, and 0.422 %. Across both HIS and SSPs, the proportions of light (75 %-78 %), moderate (18 %-21 %), and severe (4 %-5 %) DFAA events remained relatively stable. YGP, HHHP, MLYP, NCP, and NASR are the five hotspot areas. Analysis attributes 45 % (P < 0.05) of DFAA frequency variability to drought and flood frequency (74.45 %) and duration (25.55 %). Furthermore, low to medium emission scenarios show significant potential to reduce DFAA occurrence, offering direction to mitigate the impacts of global warming, particularly as mid-latitude regions have emerged as DFAA hotspots over the past 30 years. These findings provide critical insights for countries addressing climate change and ensuring food security.